The Intervention of Supportive Educative System Based on Family Centered Care Toward Family Support In Caring For Children With Leukemia In RSUD Tangerang - titik setiyaningrum; Titi Sulastri; Heny Purwanti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
The series of medical treatment procedure in children with leukemia need more longer time or period by doing the intensive chemotherapy, so that the children have hospitalization over and over again which takes a risk to irritate their self-growing and causes a distress on healing process. The purpose of this research is to analyze the intervention effect in supportive educative system based on family centered care toward family support to relieve children anxiety with leukimia. This research method is using quasi experimental method with non equivalent control group before after design approach and the number of samples from each group is 24. Taking samples is done by consecutive sampling technique. The result of this research shows the average number of children ages in both of groups are six years old. The parent ages are approximately 35-36 years old and the low basic education happened to the majority of these parents. The research result is got p value 0.000 (> 0.05) which means there is a big difference in family support system between intervention group and control after giving intervention. It can be concluded that giving intervention to the supportive educative system based on family centered care takes effect toward family support in caring for children with leukemia.